Evaluation of Therapy Management and Patient Compliance in Postmenopausal Patients with Hormone Receptor-positive Breast Cancer Receiving Letrozole Treatment: The EvaluateTM Study - Fasching, Peter; Fehm, T.; Kellner, S.; De Waal, J.; Rezal, M.; Baler, B.; Baake, G.; Kolberg, H. -C; Guggenberger, M.; Warm, N.; Harbeck, N.; Wuerstlein, R.; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: The EvaluateTM study (Evaluation of therapy management and patient compliance in postmenopausal hormone receptor-positive breast cancer patients receiving letrozole treatment) is a prospective, non-interventional study for the assessment of therapy management and compliance in the routine care of postmenopausal women with invasive hormone receptor-positive breast cancer receiving letrozole. The parameters for inclusion in the study are presented and discussed here. Material and Methods: Between January 2008 and December 2009 a total of 5045 patients in 310 study centers were recruited to the EvaluateTM study. Inclusion criteria were hormone receptor-positive breast cancer and adjuvant treatment or metastasis. 373 patients were excluded from the analysis for various reasons. Results: A total of 4420 patients receiving adjuvant treatment and 252 patients with metastasis receiving palliative treatment were included in the study. For 4181 patients receiving adjuvant treatment, treatment with the aromatase inhibitor letrozole commenced immediately after surgery (upfront). Two hundred patients had initially received tamoxifen and started aromatase inhibitor treatment with letrozole at 1-5 years after diagnosis (switch), und 39 patients only commenced letrozole treatment 5-10 years after diagnosis (extended endocrine therapy). Patient and tumor characteristics were within expected ranges, as were comorbidities and concurrent medication. Conclusion: The data from the EvaluateTM study will offer a good overview of therapy management in the routine care of postmenopausal women with hormone receptor-positive breast cancer. Planned analyses will look at therapy compliance and patient satisfaction with how information is conveyed and the contents of the conveyed informatio
EVALuna2:17459